Analysis of Implementation of Procurement of Office Stationery at Bhayangkara Hospital TK II Sartika Asih Bandung - Albert Buala Zocho Marunduri; Dian Ekawati; Yuliani Yuliani (Indonesian Journal of Health Research and Development, 2023)
The implementation of ATK goods procurement starts with requests from each room, purchases of ATK goods from third parties, receipt of ATK goods and storage of ATK goods. The purpose of procurement of ATK goods is to find out the number of goods that have come out and the number of goods that are still stored in the warehouse, or to compare the number of goods issued with the number of goods in stock in the ATK Warehouse. The process of procuring ATK goods at Bhayangkara TK II Sartika Asih Hospital from the day of observation still had several problems, one of which was the delivery of goods from third parties or suppliers that did not match the order. The method used in this research is descriptive by describing the Implementation of the Procurement of Office Stationery at the Dangkara Hospital TK II Sartika Asih Bandung. The research object is office stationery items, while the research subject is the ATK warehouse unit at Bhayangkara Hospital TK II Sartika Asih. Retrieval of data by way of observation, interviews and literature study. Results: The procedure for procuring stationery items at Bhayangkara Sartika Asih Hospital, starting from the stationery warehouse staff making a plan for the need for stationery items, then submitted to the Head of the Hospital for approval. After being approved, then make a purchase order letter to then give it to the supplier that has been determined. After the goods arrive from the supplier, an inspection of the type and quantity of goods is carried out in the sorting warehouse, after which a proof of incoming goods is made. Discussion: The implementation of RSBSA procurement of goods from the results of this study discusses the purchasing procedure network, functions related to purchasing procedures, documents used in purchasing transactions, as well as supplier selection methods for purchasing ATK goods. Conclusions and Suggestions: All activities or functions of procurement of ATK goods are carried out by the ATK warehouse and are not separated from other functions.